Rethinking the Value of Residents' Councils: Observations and Lessons from an Exploratory Study - O'DWYER, CIARA MARY; TIMONEN, VIRPI (My University, 2010)
Little empirical research is available on residents? councils in care settings for older people. This article analyzes the operation of a residents? council in an Irish facility, drawing on direct observation of council meetings and interviews with resident participants and staff members. Though some participants benefited from having the opportunity to discuss their views during council meetings, few changes were introduced that affected non-participants. We identified several barriers to the successful operation of the council, including the lack of independence of the council, inadequate skills in group facilitation, staffing shortages, lack of training and management structures.
PUBLISHED
Keywords: residents' council; older people; advocacy; care; Ireland; aged-care; residents' council; older people; advocacy; care; Ireland; aged-care